2017
DOI: 10.1007/s00259-017-3867-1
|View full text |Cite
|
Sign up to set email alerts
|

18F-DOPA PET/CT and 68Ga-DOTANOC PET/CT scans as diagnostic tools in focal congenital hyperinsulinism: a blinded evaluation

Abstract: PurposeFocal congenital hyperinsulinism (CHI) is curable by surgery, which is why identification of the focal lesion is crucial. We aimed to determine the use of 18F–fluoro-dihydroxyphenylalanine (18F-DOPA) PET/CT vs. 68Ga-1,4,7,10-tetraazacyclododecane-1,4,7,10-tetraacetic-acid-1-Nal3-octreotide (68Ga-DOTANOC) PET/CT as diagnostic tools in focal CHI.MethodsPET/CT scans of children with CHI admitted to Odense University Hospital between August 2005 and June 2016 were retrospectively evaluated visually and by t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
1
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 46 publications
1
17
1
1
Order By: Relevance
“…Furthermore, the laparoscopic approach is dependent on preoperative identification of the focal lesion as predicted by heterozygous paternal K ATP -channel mutations and 18 F-DOPA-PET/CT ( 29 , 37 , 38 ). The sensitivity and specificity of these diagnostic tools do, however, not reach 100% ( 1 , 27 , 39 41 ), neither in our series (data not shown).…”
Section: Discussioncontrasting
confidence: 75%
“…Furthermore, the laparoscopic approach is dependent on preoperative identification of the focal lesion as predicted by heterozygous paternal K ATP -channel mutations and 18 F-DOPA-PET/CT ( 29 , 37 , 38 ). The sensitivity and specificity of these diagnostic tools do, however, not reach 100% ( 1 , 27 , 39 41 ), neither in our series (data not shown).…”
Section: Discussioncontrasting
confidence: 75%
“…18-fluoro-dopa positron-emission tomography (PET)-computed tomography [or PET-magnetic resonance imaging (MRI)] is the current best investigation method with which to identify and localize focal lesions [27], although there can be lack of agreement on the results. The scan differentiates between focal and non-focal aetiology but is unable to separate normal pancreas from that of diffuse CHI.…”
Section: Histological Descriptions Of Congenital Hyperinsulinism: Focmentioning
confidence: 99%
“…The sensitivity for detecting focal lesions varies between 88 and 94% with an accuracy of 100% ( 175 ). In a recent study 18 F-DOPA-PET/CT was found to be superior in localizing focal lesions compared to imaging with 68 Ga-DOTANOC PET/CT ( 176 ). Patients with focal CHI are usually unressponsive to medical therapy and require a surgical lesionectomy.…”
Section: Introductionmentioning
confidence: 99%